The School administrator's guide to information power [videorecording] - Bynum, Bill.; Wrisley, John. ([Columbia, S.C.] University of South Carolina, 1989)
A panel discussion on the value and power of information. It draws the comments and reactions of school administrators who agree that information power is a partnership of technology, resources and people.
VHS.
Moderator, John Wrisley.
Keywords: Media programs (Education).; Education; School management